Efektivitas Media Promosi “Piring Makanku” Pedoman Gizi Seimbang Sebagai Panduan Sekali Makan (The Effectiveness of Media promotion "Piring Makanku" Balanced Nutrition Guidelines as a Guide Once Packed) - Pravasta Ade Pratama; Elfian Zulkarnain; Mury Ririanty (Pustaka Kesehatan, 2018)
Abstract The problem of nutrition in Indonesia currently has entered a double nutritional problems i.e. less nutritional problems and excess nutritional problems. Is a group of kids who are prone to more nutrition. Department of health’s strategic plan outlines the goals of health promotion 2005-2009 with principal activities the development of health promotion and media communication technology, information and education (KIE). The Government issued a Balanced Nutritional Guidelines contained media promotion "Tumpeng" and "Piring Makanku" in an attempt to lower and maintain the nutritional status of the public. This research aims to analyze the effectiveness of media promotion "Piring Makanku". This research was quantitative research semi experimental at SDN Jember Lor 1. Data analysis was the analysis of the statistical test of Wilcoxon Signed Rank Test and Mann Whitney with α = 0.05. The results showed that the media "Piring Makanku" effective in improving knowledge, attitudes and practice towards a balanced nutrition. Keywords: The Effectiveness of Media, Piring Makanku, Knowledge, Attitudes, Practice